Body weight estimation from various footprint length measurements among Ibans of east Malaysia - T. Nataraja Moorthy,; Hairunnisa Mohd Anas Khan, (Malaysian Society of Applied Biology, 2016)
Foot impressions are still found at crime scenes. The foot impressions can be used to estimate stature, gender and body weight of an individual. Most of the foot/foot print studies were conducted on mixed population. But racial and cultural aspects of foot morphology must be considered while conducting such studies. Hence the present study aims to estimate body weight from bilateral footprints collected from 240 (120 males, 120 females) consenting adult Iban ethnics, an indigenous groups residing in east Malaysia. Informed consent and Human Ethical Approval were obtained. The body weight of the living individuals and footprints were collected following the standard procedure. The data obtained were analyzed with PASW 20 computer software and derived regression formulae to estimate body from footprint lengths of Iban population. Investigation revealed that all footprint lengths exhibit statistically positive significant correlation with body weight (p<0.001). Correlation coefficient (R) values are found to be higher in the pooled sample (0.262–0.356) when compared with males (0.082–0.338) and females (0.104–0.249). The regression formulae derived for the pooled sample can be used to estimate body weight when the sex of the footprint remains unknown, as in real crime scenarios.